Association Mapping Reveals Genetic Loci Associated with Important Agronomic Traits in Lentinula edodes, Shiitake Mushroom - Li, Chuang; Gong, Wenbing; Zhang, Lin; Yang, Zhiquan; Nong, Wenyan; Bian, Yinbing; Kwan, Hoi-Shan; Cheung, Man-Kit; Xiao, Yang (Frontiers in Microbiology, 2017)
Association mapping is a robust approach for the detection of quantitative trait loci. Here, by genotyping 297 genome-wide molecular markers of 89 Lentinula edodes cultivars in China, the genetic diversity, population structure and genetic loci associated with 11 agronomic traits were examined. A total of 873 alleles were detected in the tested strains with a mean of 2.939 alleles per locus, and the Shannon’s information index was 0.734. Population structure analysis revealed two robustly differentiated groups among the Chinese L. edodes cultivars (FST = 0.247). Using the mixed linear model, a total of 43 markers were detected to be significantly associated with four traits. The number of markers associated with traits ranged from 9 to 26, and the phenotypic variations explained by each marker varied from 12.07% to 31.32%. Apart from five previously reported markers, the remaining 38 markers were newly reported here. Twenty-one markers were identified as simultaneously linked to two to four traits, and five markers were associated with the same traits in cultivation tests performed in two consecutive years. The 43 traits-associated markers were related to 97 genes, and 24 of them were related to 10 traits-associated markers detected in both years or identified previously, 13 of which had a > 2-fold expression change between the mycelium and primordium stages. Our study has provided candidate markers for marker-assisted selection and useful clues for understanding the genetic architecture of agronomic traits in the shiitake mushroom.